2017
DOI: 10.1107/s2056989017006363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of a new magnesium phosphate Na3RbMg7(PO4)6

Abstract: Trisodium rubidium hepta­magnesium hexakis(ortho­phosphate) exhibits a new structure type, with MgOx (x = 5 and 6) polyhedra linked directly to each other through common corners or edges and reinforced by corner-sharing with PO4 tetra­hedra. The resulting anionic three-dimensional framework leads to the formation of channels in which the Na+ cations are located, while the Rb+ cations are located in large inter­stitial cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…1(a), while the crystallographic data of Na 3 RbMg 7 (PO 4 ) 6 was used as the initial modal. 32 All the diffraction peaks of the experimental data have a good agreement with the calculated data except for the intensity. And the relevant refined residual factors are R wp = 8.41%, R p = 7.18%, and χ 2 = 1.462, which maintains a low level.…”
Section: Resultssupporting
confidence: 62%
“…1(a), while the crystallographic data of Na 3 RbMg 7 (PO 4 ) 6 was used as the initial modal. 32 All the diffraction peaks of the experimental data have a good agreement with the calculated data except for the intensity. And the relevant refined residual factors are R wp = 8.41%, R p = 7.18%, and χ 2 = 1.462, which maintains a low level.…”
Section: Resultssupporting
confidence: 62%
“…where A = K, Rb, Cs; M = Fe 2+ , Mg, Mn, Zn (Yakubovich et al 1996;Queen et al 2007;Guo et al 2014;Ben Hamed et al 2017). The direct chemical analogue of xenophyllite was reported by Pu et al (2019).…”
Section: Discussion: Structural Links Between Yakubovichite Galileiit...mentioning
confidence: 99%
“…In 2017, Hamed et al first reported Na 3 RbMg 7 (PO 4 ) 6 with a monoclinic system and a C 2/ c space group. 193 As shown in Fig. 15a, the Na 3 RbMg 7 (PO 4 ) 6 consists of MgO x frameworks by sharing edges or corners.…”
Section: Different Types Of Ce3+/eu2+ Doped Phosphorsmentioning
confidence: 99%